A Self‐Assembled Heterometallic Co7–Ho1 Nanocluster: 3d‐4f Trimeric Keggin‐Type Silicotungstate [HoCo7Si3W29O108(OH)5 (H2O)4]18– and its Catalytic and Magnetic Applications. Issue 3 (5th December 2018) - Das, Vivek; Khan, Imran; Hussain, Firasat; Sadakane, Masahiro; Hageo, Kazuki; Ichihashi, Katsuya; Inoue, Katsuya; Nishihara, Sadafumi
Abstract : A new self assembled Co 2+ and Ho 3+ ‐substituted polyoxometalate have been synthesized using a trilacunary Keggin‐type silicotungstate. The polyanion complex of the formula [HoCo7 Si3 W29 O108 (OH)5 (H2 O)4 ] 18– (1) has a trimeric crystal structure which displayed an excellent catalytic and magnetic property. Here, we have carried out selective oxidation of various alcohol substrates such as derivatives of benzyl alcohol, cyclohexanol etc. to its corresponding aldehydes/ketones. The paramagnetic nature of the compound was seen from the magnetic study. However, antiferromagnetic interaction was observed between Co 2+ ‐Co 2+ or Co 2+ ‐Ho 3+ at a very low temperature. The compound was characterized by FT‐IR, UV/Visible spectroscopy, Single crystal X‐ray diffraction, X‐ray powder diffraction, high‐resolution electrospray ionization mass spectroscopy (HR‐ESI‐MS) and thermogravimetric analysis (TGA). Abstract : A novel self‐assembled Keggin‐type heterometallic 3d‐4f silicotungstate nanocluster [HoCo7 Si3 W29 O108 (OH)5 (H2 O)4 ] 18– have been synthesized in a conventional one‐pot synthetic procedure which displayed an excellent applications in the field of catalysis and magnetism.